(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
Corporate governance is the foundation through which the success of organizations is advanced, especially in a world characterized by globalization and rapid technological changes. It ensures efficiency in resource allocation, enhances transparency, and builds stakeholder trust, thus being a factor that makes competition feasible.